Oxidative Stress Evaluation in Dogs Affected with Canine Monocytic Ehrlichiosis - Michela Pugliese; Vito Biondi; Giordana Merola; Alessandra Landi; Annamaria Passantino (MDPI AG, 2022)
The study aimed to evaluate the concentration of reactive oxidative metabolites (R-OOHs), the antioxidant barrier (OXY), and the ratio between R-OOHs and OXY (OSi) and thiol groups of plasma compounds (SHp) in in canine monocytic ehrlichiosis. Thirty dogs affected with monocytic ehrlichiosis (canine monocytic ehrlichiosis group-CME group) and ten healthy dogs (control group-CTR group) were evaluated. CME was diagnosed by the presence of clinical signs and the detection of anti-Ehlichia canis antibodies. Oxidative stress parameters of two groups were compared using the Mann-Whitney test. Significance was set at p < 0.05. Spearman rank correlation was performed to analyze oxidative stress, and hematological and biochemical variables in the CME group. All dogs affected with CME showed a wide spectrum of clinical signs such as lethargy, anorexia, fever, weight loss, lymph adenomegaly, splenomegaly, subcutaneous and mucosal petechial and ecchymosis, and vomiting. Anaemia, leukocytosis, thrombocytopenia, hyperglobulinemia, hypoalbuminemia and an increase of blood urea nitrogen and creatinine are also detected. Results showed significantly lower values of SHp in the CME group than in CTR. A statistically significant difference in the number of white blood cells, platelets, and blood urea nitrogen concentration was assayed comparing to the two groups. A negative correlation between SHp and hemoglobin concentration was recorded. These preliminary results may suggest a possible function of oxidative stress in the onset of clinical signs during the course of CME.